Des oueds mythiques aux rivières artificielles : l'hydrographie du Bas-Sahara algérien - Jean-Louis Ballais (Physio-Géo)
New researches on Bas-Sahara hydrography have been performed. They show that mythical wadis such as wadi Igharghar from south of the Grand Erg Oriental, wadi Mya close to Ouargla and wadi Rhir do not exist. Among the functional real wadis, those that run from the saharan Atlas mountains are best known, due to their dams. Those of the M'Zab ridge are still poorly studied. Fossil real wadis have been just discovered in the Souf region, north of the Grand Erg Oriental. The only genuine perennial rivers, such as the grand drain, are fed by oasis collature waters and towns rainwater networks.